(untitled) (Bioagro, 2026)
Peru is considered the main producer of olives (Olea europaea) in South America, and Tacna is the leading region with over 23,000 hectares under cultivation. The objective of this research was to evaluate the effect of two drip irrigation systems (double-row - DH and sectorized - ST) on rhizospheric fungi and plant productivity. Fungi were isolated from soil samples, and olive yield, fruit weight, and dry matter content (%) were assessed as a function of the irrigation type using a t-test with 20 replications. Twenty-two fungal morphotypes were isolated from the genera Alternaria (2), Cladosporium (1), Fusarium (4), Paecilomyces (5), Trichoderma (8), and Verticillium (1). There was a trend toward a greater number of strains in the ST compared to the DH system. The irrigation ST resulted in a higher yield than DH (p≤0.05), with 5,020 versus 4,417 kg·ha⁻¹. On the other hand, DH produced a higher average fruit weight than ST, with 7.899 g versus 7.183 g. Finally, the plant organs under ST irrigation had a higher dry matter fraction, with 31.30 and 22.63 % in branches and leaves, respectively, compared to 28.33 and 19.37 % under DH irrigation. Furthermore, positive correlations ranging from r = 0.95 to r = 0.54 (p≤0.05) were found between the productivity variables. This study suggests that, in terms of yield, the ST irrigation is a better option for olive irrigation in the saline soils of the Tacna region.